Penanganan Sengketa Persyaratan Pemilihan Kepala Desa di Jaten, Kabupaten Blitar - Tarisha Nur Azizah; Septiya Eka Wardani; Arga Adriansah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research examines dispute resolution related to incomplete requirements in the election of village heads in Jaten, Blitar Regency. The main focus is analysis of the environmental settlement process, the factors that influence decisions, and their impact on the stability and legitimacy of local government. Research methods include case studies and documentaries to understand the analysis of legal mechanisms and practices used in dealing with this kind of settlement. It is hoped that the research results will provide in-depth insight into the village head election resolution process, as well as provide recommendations for improving the system to be more transparent and inclusive.